Optimization of a Benzothiazole Indolene Scaffold Targeting Bacterial Cell Wall Assembly - Chauhan J; Yu W; Cardinale S; Opperman TJ; MacKerell AD Jr; Fletcher S; de Leeuw EPH (Dove Medical Press, 2020)
Jay Chauhan,1 Wenbo Yu,2 Steven Cardinale,3 Timothy J Opperman,3 Alexander D MacKerell Jr,2,4 Steven Fletcher,1 Erik PH de Leeuw1 1Institute of Human Virology & Department of Biochemistry and Molecular Biology of the University of Maryland Baltimore School of Medicine, Baltimore, MD 21201, USA; 2Computer-Aided Drug Design Center, University of Maryland, School of Pharmacy, Baltimore, MD 21201, USA; 3Microbiotix, LLC., Worcester, MA 01605, USA; 4Department of Pharmaceutical Sciences, University of Maryland, School of Pharmacy, Baltimore, MD 21201, USACorrespondence: Erik PH de LeeuwTel +1 410 706 3430Email edeleeuw@som.umaryland.eduBackground: The bacterial cell envelope is comprised of the cell membrane and the cell wall. The bacterial cell wall provides rigidity to the cell and protects the organism from potential harmful substances also. Cell wall biosynthesis is an important physiological process for bacterial survival and thus has been a primary target for the development of antibacterials. Antimicrobial peptides that target bacterial cell wall assembly are abundant and many bind to the essential cell wall precursor molecule Lipid II.Methods: We describe the structure-to-activity (SAR) relationship of an antimicrobial peptide-derived small molecule 7771– 0701 that acts as a novel agent against cell wall biosynthesis. Derivatives of compound 7771– 0701 (2-[(1E)-3-[(2E)-5,6-dimethyl-3-(prop-2-en-1-yl)-1,3-benzothiazol-2-ylidene]prop-1-en-1-yl]-1,3,3-trimethylindol-1-ium) were generated by medicinal chemistry guided by Computer-Aided Drug Design and NMR. Derivatives were tested for antibacterial activity and Lipid II binding.Results: Our results show that the N-alkyl moiety is subject to change without affecting functionality and further show the functional importance of the sulfur in the scaffold. The greatest potency against Gram-positive bacteria and Lipid II affinity was achieved by incorporation of a bromide at the R3 position of the benzothiazole ring.Conclusion: We identify optimized small molecule benzothiazole indolene scaffolds that bind to Lipid II for further development as antibacterial therapeutics.Keywords: Lipid II, antibiotics, drug development, cell wall